The effect of feed restriction on the fat profile of Santa Inês lamb meat - Marta Suely Madruga; Taliana Kênia Alves Bezerra; Ingrid Conceição Dantas Guerra; Ana Sancha Malveira Batista; Aderbal Marcos de Azevedo Silva; Rafaella de Paula Paseto Fernandes (Acta Scientiarum: Animal Sciences, 2020)
Consumers today are increasingly more demanding regarding their food, seeking healthier and better quality products, and in this context animal nutrition plays a key role. The meat composition can be altered by animal feed itself, being that lipid profile may directly contribute to consumer health, reducing the predisposition of developing cardiovascular diseases, main cause of mortality in the world. Thus, the aim of this study was to assess the effect of dietary feed restriction in Santa Inês lambs on their intramuscular, intermuscular, and subcutaneous fat profile, fat profile of the longissimus thoracis et lumborum (LTL) muscle, and the total meat lipids and cholesterol. Three groups of lambs were subjected to diets: without restriction (WR), and 30 and 60% feed restriction. Overall, stearic, palmitic, and oleic acids were the predominant and the lowest lipid and cholesterol levels were observed at the highest restriction level, presenting higher polyunsaturated:saturated (PUFA:SFA) and desirable (DFA) fatty acid ratios (p < 0.05). Lambs subjected to 60% dietary feed restriction had a better quality meat with lower lipid and cholesterol contents, and profile favorable for human health due the presence of unsaturated fatty acids, that is important parameter the market demands to meet the consumers’ expectations.